Correction: Protective porcine influenza virus-specific monoclonal antibodies recognize similar haemagglutinin epitopes as humans. - Barbara Holzer; Pramila Rijal; Adam McNee; Basudev Paudyal; Veronica Martini; Becky Clark; Tanuja Manjegowda; Francisco J Salguero; Emily Bessell; John C Schwartz; Katy Moffat; Miriam Pedrera; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1009330.].